Pea Efficiency of Post-drought Recovery Relies on the Strategy to Fine-Tune Nitrogen Nutrition - Couchoud, Mégane; Salon, Christophe; Girodet, Sylvie; Jeudy, Christian; Vernoud, Vanessa; Prudent, Marion (Frontiers in Plant Science, 2020)
As drought is increasingly frequent in the context of climate change it is a major constraint for crop growth and yield. The ability of plants to maintain their yield in response to drought depends not only on their ability to tolerate drought, but also on their capacity to subsequently recover. Post-stress recovery can indeed be decisive for drought resilience and yield stability. Pea (Pisum sativum), as a legume, has the capacity to fix atmospheric nitrogen through its symbiotic interaction with soil bacteria within root nodules. Biological nitrogen fixation is highly sensitive to drought which can impact plant nitrogen nutrition and growth. Our study aimed at dynamically evaluating whether the control of plant N status after drought could affect nodulated pea plant’s ability to recover. Two pea genotypes, Puget and Kayanne, displaying different drought resilience abilities were compared for their capacity to tolerate to, and to recover from, a 2-weeks water deficit period applied before flowering. Physiological processes were studied in this time-series experiment using a conceptual structure-function analysis framework focusing on whole plant carbon, nitrogen and water fluxes combined to two 13CO2 and 15N2 labelling experiments. While Puget showed a yield decrease compared to well-watered plants, Kayanne was able to maintain its yield. During the recovery period, genotype-dependent strategies were observed. The analysis of the synchronisation of carbon, nitrogen and water related traits dynamics during the recovery period and at the whole plant level, revealed that plant growth recovery was tightly linked to N nutrition. In Puget, the initiation of new nodules after water deficit was delayed compared to control plants, and additional nodules developed, while in Kayanne the formation of nodules was both rapidly and strictly re-adjusted to plant growth needs, allowing a full recovery. Our study suggested that a rapid re-launch of N acquisition, associated with a fine-tuning of nodule formation during the post-stress period is essential for efficient drought resilience in pea leading to yield stability.